Authentic Literature in Textbooks of Czech as a Foreign Language - SACHROVÁ , Kateřina (Bohemistyka, 2021)
Usage of the literary style is an important part of teaching and learning Czech as a native or foreign language. The literary style, or more exactly, the style of literature, drama and poetry, is an important way of that representing the culture at the basis of the taught language. In this paper, we provide a short outline of the problem of authenticity in textbooks of Czech as a foreign language. The aim of this article is to present some of the aspects of using authentic literary texts in modern communicative textbooks. The study is based on analysis of the textual content of contemporary teaching materials.